2017
DOI: 10.1038/ng.3885
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic burdens on cell-specific pathways underlie the risk of rheumatoid arthritis

Abstract: Recent evidence suggests that a substantial portion of complex disease risk alleles modify gene expression in a cell-specific manner. To identify candidate causal genes and biological pathways of immune-related complex diseases, we conducted expression quantitative trait loci (eQTL) analysis on five subsets of immune cells (CD4 T cells, CD8 T cells, B cells, natural killer (NK) cells and monocytes) and unfractionated peripheral blood from 105 healthy Japanese volunteers. We developed a three-step analytical pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
116
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 130 publications
(123 citation statements)
references
References 39 publications
6
116
1
Order By: Relevance
“…In a recent article in Arthritis & Rheumatology , Thalayasingam et al reported that the 6p23 locus, associated with rheumatoid arthritis (RA), has a B cell–specific expression quantitative trait locus (eQTL) effect on CD83. The B cell–specific eQTL effect at this locus is robust and has also been reported by others , and it presumably contributes to the pathogenesis of RA by decreasing the expression of CD83 on B cells. We sought to determine the basis for the B cell–specific eQTL effect and to further elucidate the mechanism by which it contributes to RA pathogenesis.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…In a recent article in Arthritis & Rheumatology , Thalayasingam et al reported that the 6p23 locus, associated with rheumatoid arthritis (RA), has a B cell–specific expression quantitative trait locus (eQTL) effect on CD83. The B cell–specific eQTL effect at this locus is robust and has also been reported by others , and it presumably contributes to the pathogenesis of RA by decreasing the expression of CD83 on B cells. We sought to determine the basis for the B cell–specific eQTL effect and to further elucidate the mechanism by which it contributes to RA pathogenesis.…”
supporting
confidence: 77%
“…CD83 regulates the development of murine B cells . We therefore hypothesized that CD83 expression might influence the development of human B cells, and we examined the relationship between this haplotype and peripheral blood B cells in healthy subjects from our data set . Individuals with the RA risk SNP had an increased frequency of CD27−IgD− double‐negative B cells (Figure B), a subset that is increased in the peripheral blood of RA patients and thought to be pathogenic .…”
mentioning
confidence: 99%
“…In addition to the above‐mentioned analyses, ChIP‐Atlas Enrichment Analysis (formerly designated “ in silico ChIP”) has been used for various other purposes. For example, this tool has been applied to analyze TR enrichment at genomic ROIs such as expression quantitative trait loci (eQTLs), a user's own ChIP‐seq peak‐call data, and evolutionarily accelerated regions as well as genes whose expression levels are changed by drug exposure, aging, or cancer development (see http://chip-atlas.org/publications for the full list of publications citing ChIP‐Atlas). The results generated by ChIP‐Atlas are all assigned unique URLs (see ChIP‐Atlas document in https://github.com/inutano/chip-atlas/wiki for details) and are publicly available, and they are thus ready for sharing seamlessly among researchers for subsequent analysis in command lines and for interconnecting with other biodatabases such as the DeepBlue Epigenomic Data Server and RegulatorTrail , where ChIP‐Atlas data have been imported and subjected to analyses.…”
Section: Resultsmentioning
confidence: 99%
“…These variants, named expression quantitative trait loci (eQTL), provide a functional relevance for the association between genetic variants and AIDs. The eQTL analysis was recently applied to rheumatoid arthritis (RA) and successfully predicted the importance of the tumor necrosis factor (TNF) pathway in CD4 + T cells . Although eQTLs have never been studied directly for MG, a screen of cis ‐eQTLs for 353 AID risk variants in 42 human thymic tissues identified eight eQTLs associated with seven genetic regions, including two regions that were thymus specific .…”
Section: Typical Molecular Signatures In Mg and Other Aidsmentioning
confidence: 99%